FAKTOR FAKTOR YANG MEMPENGARUHI PENDAPATAN UMKM PANDAN WANGI DI DESA TUMBAKBAYUH KECAMATAN MENGWI KABUPATEN BADUNG - I Made Hary Kusmawan; Ni Putu Juniari (Badung: LPPM Universitas Triatma Mulya, 2020)
Micro, Small and Medium Enterprises (MSMEs) are an important part of a country's economy. This important role has encouraged many countries including Indonesia to continue to strive to develop MSMEs. The objectives of this study were(1) To determine whether the length of business had a partial effect on the income of Pandan Wangi MSMEs in Tumbakbayuh Village, Mengwi District, Badung Regency, (2) To determine whether the number of workers had a partial effect on the income of Pandan Wangi MSMEs in the Village. Tumbakbayuh, Mengwi District, Badung Regency, and (3) To find out whether the length of effort and the number of workers have a simultaneous effect on the income of Pandan Wangi MSMEs in Tumbakbayuh Village, Mengwi District, Badung Regency. The samples in this study were all Pandan Wangi SMEs in Tumbakbayuh Village, Mengwi District, Badung Regency using the saturated sample method, with the analysis technique using multiple linear regression. Based on the results of the analysis of the length of business, it has a partial effect on the income of SMEs Pandan Wangi in Tumbakbayuh Village, Mengwi District, Badung Regency, because the t-count value is greater than the t-table value or the -t-count value is smaller than the -t table value, the number of workers has a partial effect. on the income of Pandan Wangi MSMEs in Tumbakbayuh Village, Mengwi District, Badung Regency, because the t count value is greater than the t table value or the -t count value is smaller than the -t table value, the length of business and the number of workers have a simultaneous effect on the income of MSMEs Pandan Wangi in Tumbakbayuh Village, Mengwi District, Badung Regency, because the calculated F value is greater than the F table value.